Oxygen isotope analysis of human bone phosphate evidences weaning age in archaeological populations. Issue 2 (11th February 2015) - Britton, Kate; Fuller, Benjamin T.; Tütken, Thomas; Mays, Simon; Richards, Michael P.
ABSTRACT Here we report bone phosphate oxygen (δ18Op) values from perinates/neonates and infants (<3.5 years; n = 32); children (4–12 years; n = 12); unsexed juveniles (16–18 years; n = 2); and adult bones (n = 17) from Wharram Percy, North Yorkshire, England, in order to explore the potential of this method to investigate patterns of past breastfeeding and weaning. In prior studies, δ15N and δ13C analyses of bone collagen have been utilized to explore weaning age in this large and well‐studied assemblage, rendering this material highly appropriate for the testing and development of this alternative method targeting the inorganic phase of bone. Data produced reveal 18O‐enrichment in the youngest perinatal/neonatal and infant samples, and an association between age and bone δ18Op (and previously‐published δ15N values), with high values in both these isotope systems likely due to breastfeeding. After the age of 2–3 years, δ18Op values are lower, and all children between the ages of 4 and 12, along with the vast majority of sub‐adults and adults sampled (aged 16 to >50 years), have δ18Op values consistent with the consumption of local modern drinking water. The implications of this study for the reconstruction of weaning practices in archaeological populations are discussed, including variations observed with bone δ15Ncoll and δ18Op co‐analysis and the influence of culturally‐modified drinking water and seasonality. The use of this method to explore human mobility and palaeoclimatic conditions are also discussed with reference to the data presented. Am J Phys Anthropol 157:226–241, 2015. © 2015 Wiley Periodicals, Inc.